Association between site‐specific muscle loss of lower body and one‐leg standing balance in active women: The HIREGASAKI study. Issue 2 (8th July 2013) - Abe, Takashi; Ogawa, Madoka; Loenneke, Jeremy P; Thiebaud, Robert S; Loftin, Mark; Mitsukawa, Naotoshi
<x xml:space="preserve">Abstract</x> Aim To test the hypothesis that static balance is associated with site‐specific loss of muscle mass in older adults. Methods A total of 57 active women aged 52–83 years had their muscle thickness (MTH) measured by ultrasound at four sites on the anterior and posterior aspects of their upper‐ and lower‐leg. MTH ratios were calculated to assess the site‐specific muscle loss. One‐leg standing balance with eyes open and maximum isometric knee extension/flexion strength were measured. Daytime physical activity was also measured. The participants were separated into three groups based on achieved timed one‐leg balance test: less than 60 s (n = 19, G1), 60–120 s (n = 12, G2) and over 120 s (n = 26, G3). Results Age was inversely correlated to the upper‐leg (A50 : P70) MTH ratios (r = −0.389, P < 0.001), but not lower‐leg ratio (r = 0.047), thus site‐specific muscle loss was observed in the upper‐leg. Total muscle mass was similar among the groups. A50 : P70 MTH ratio and absolute and relative knee flexion strength were lower in G1 than in G3. Step counts and durations of moderate and vigorous exercise were lower in G1 and G2 than in G3. There were significant correlations between one‐leg balance and A50 : P70 MTH ratio (r = 0.271, P < 0.05) and physical activity level (r = 0.357–0.481, P < 0.01). After adjusting for step count, one‐leg balance was only correlated significantly with duration of vigorous exercise (r = 0.319, P < 0.05). Conclusion Higher physical activity could have more impact on balance regulation, as the influence of site‐specific muscle loss was weak in active women. Geriatr Gerontol Int 2014; 14: 381–387.